Analysis of the conduct of Dentistry academics in the service of serum positive patients (Research, Society and Development, 2021)
The objective is to evaluate the knowledge and conduct adopted by dentistry students regarding the care of HIV-positive patients. This is a cross-sectional, quantitative study, carried out between June and December 2020. The work was approved by the Ethics Committee of the UNIFACID University Center under the number 075913/2020. Data were collected through the application of a questionnaire to dentistry students from the 6th to the 10th period of a University Center in Teresina. The data were tabulated in Excel® and analyzed descriptively. 97 students participated, predominantly female (73.2%, n=71), aged 20-29 years (93.8%, n = 91), who use the mask and cap (79.4%, n=77), surgical gown (86.6%, n=84) and gloves (82.5%, n=80). The majority (85.6%, n=83) confirmed that they received positive serum patients, even though they showed concern about the risk of infection (96.9%, n=94). A part (18.6%; n=18) reported having suffered injury with sharp material, however, only 8.2% (n=8) underwent anti-HIV testing. As for the care adopted: 94.8% (n=92) would conduct sanitizing with water and soap and the use of antiseptics (81.4%, n=79). There was no consensus on the right to deny the service, the amount charged and the environment indicated for the service, but all are safe and prepared to manage the patient with positive serum, insecure to bloody procedures (59.8%, n=58) and diagnosis of oral lesions (51.5%, n=50). Academics are concerned about the risks, but they show scientific and technical knowledge about the disease, which makes them show safety in the care of positive serum patients.